Treatment Adherence among Hypertensive Patients Attending in a Tertiary Care Hospital of Bharatpur, Chitwan - Thapa, Sara; Ghimire, Srijana; KC Shrestha, Soni (Journal of Bharatpur Hospital, 2026)
BackgroundHypertension is a major global health problem and a key risk factor for cardiovascular diseases, with poor control in low- and middle-income countries. Poor medication adherence leads to uncontrolled blood pressure and complications. This study aimed to assess status of treatment adherence among hypertensive patients in a tertiary care hospital.MethodsA analytical cross sectional study was conducted among hypertensive patients attending the Cardiac Outpatient Department (OPD). A total of 131 patients were selected using a non-probability convenience sampling technique. Data were collected from December 25, 2025, to February 25, 2026, using a structured interview schedule. The Hill-Bone Medication Adherence Scale was used to assess treatment adherence. Data were analyzed using Statistical Package for the Social Sciences (SPSS) version 16 with descriptive and inferential statistics. ResultsMost respondents (60.3%) were older adults and 55.0% were female. A majority (42.0%) had informal education, and 55.1% had hypertension for over five years. More than half (61.1%) reported medication costs as unaffordable, and only 37.4% had participated in awareness programs. Only 48.9% were adherent to treatment in which presence of diabetes (p= 0.044) and number of prescribed medications per day (p = 0.024) showed were significant association with treatment adherence.ConclusionsMore than half of hypertensive patients had imperfect adherence. Strengthening awareness programs and adherence counselling regarding hypertensive medication during each visit may improve adherence and overall disease management.